Cyto-Morphological Investigations in Piper Spp. - Ambili Anand (Department of Plantation Crops and Spices, College of Horticulture, 1997)
The study 'Cyto-morphological investigations in Piper spp.' was conducted in the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara during the period from October 1994 to December 1996. The major objectives were to prepare morphological descriptors for the eight Piper spp. collected from different geographical areas and to conduct cytological investigations in these species. To prepare morphological descriptors for the eight species studied detailed morphological observations were recorded. Based on the salient observations on morphology brief descriptions of the eight Piper spp. were made. The eight species of Piper studied were analysed for the similarities and differences in their morphological characters to find out the relationship among the species. Based on morphological comparisons, a key for identification of species has been proposed. The procedure for mitotic studies in Piper spp. was standardised. The roots were collected between 11.15 a.m. and 12.15 p.m. and pre-treated in 8- hydroxyquinoline for two to three hours at 40 C. The pre-treated roots were fixed in Carnoy's A or Carnoy's B for one or two days. The material was then hydrolysed in 1 N hydrochloric acid in a water bath maintained at a temperature of 600C for fifteen minutes. The roots were then stained in 0.5% acetoorcein for 45 minutes. After that